Acute Structural Repercussions of Vertical Ladder Training on the Muscle Belly of Wistar Rats after Joint Immobilization - Grillo, Bruna Aléxia Cristofoletti [UNESP]; Tomiate, André Neri [UNESP]; Pimentel Neto, Jurandyr [UNESP]; da Silva, José Roberto Rodrigues [UNESP]; Polican Ciena, Adriano [UNESP] (Edra SpA, 2025)
Background. Resistance training promotes positive musculoskeletal adaptations that reverse changes in long-term muscle atrophy, elucidating the progression and coor-dination of acute muscle remodeling caused by resistance training without additional load. Objective. The aim was to describe the morphological changes and the acute period of remodeling in the gastrocnemius muscle, after muscular atrophy caused by joint immobilization and intervention with vertical ladder training in Wistar rats. Methods. Sixty-five 60-day-old Wistar rats were divided into: Control (C); Trained (T); Immobilized (I); Post-immobilization (PI); Trained Immobilized (TI). The groups were analyzed in 4 periods (0-hours, 24-hours, 4-days, and 7-days), therefore, the animals had intervention levels of the protocols. By light microscopy were measured the complexity of the nuclei through fractal dimension (FD), quantification of connective tissue, and with Myofibrillar ATPase, the cross-sectional area (CSA) of type I and II fibers. Results. Isolated training promoted less FD (T0h) followed by an increase (T24h), reduction of the connective tissue (T0h) with accentuated increase (T24h), and progression of CSA (TI0h, TI24h, TI4d, TI7d). Immobilization resulted in reduced FD (I0h), an increase in connective tissue (I0h), and reductions in muscle fiber CSA (I0h, PI24h). While training after atrophy promoted an increase in the FD (TI0h), variations in the connective tissue (TI0h, TI4d, TI7d), and an increase in CSA (TI0h, TI4d, TI7d). Conclusions. Resistance training promoted changes in the myonuclei, connective tissue, and CSA of muscle fibers since the 1st session, which inhibits the progression of atrophic effects even after interruption of the atrophy protocol.
Keywords: immobilization; intramuscular connective tissue; morphometry; Muscle atrophy; resistance training